Haematological and biochemical alterations in leprosy patients already treated with dapsone and MDT - Queiroz, Regina Helena Costa; Melchior Júnior, Enzo; Souza, Ana Maria de; Gouveia, Elias; Barbosa, José Carlos; Carvalho, Dermeval de (Elsevier, 1997)
Dapsone (DDS) is useful in the treatment of a number of inflammatory conditions which are characterized by neutrophil infiltration. It is the drug of choice for the treatment of leprosy and prophylaxis of malaria. Haematological side effects of methaemoglobinaemia and haemolysis have been long recognized. However, the frequency and severity of these side effects in patients already treated with DDS as a single drug or as part of a multidrug therapy (MDT) have not been well documented. We report herein an investigation of the effect of dapsone long-term treatment on the haematological and biochemical alterations in leprosy patients undergoing dapsone as a single drug (DDS group) or as part of a multidrug therapy in combination with rifampin and clofazimine (MDT group). Methaemoglobinaemia and haemolytic anaemia were the principal side effects observed. Reticulocytes were found to be elevated (> 1.5%) in 90% of the patients. Heinz bodies were also detected (6.6% of the patients). The osmotic fragility test showed a reduction in cell resistance and in the evaluation of white cells a severe eosinophilia was found. Hepatic, pancreatic and renal evaluation by the determination of biochemical parameters showed rare and occasional changes of no apparent clinical significance. We conclude that haematological side effects of dapsone are significant even at doses currently used to treat leprosy (100 mg/day) and that rifampin and clofazimine do not increase the incidence of these effects during long-term treatment.
Keywords: Dapsone; Leprosy patient; Multidrug therapy; Side effect; clofazimine; dapsone; rifampicin; clinical article; combination chemotherapy; controlled study; eosinophilia; female; hemolysis; hemolytic anemia; human; incidence; leprosy; male; methemoglobinemia; oral drug administration; side effect; Clofazimine; Drug Therapy, Combination; Female; Humans; Leprostatic Agents; Leprosy; Male; Methemoglobinemia; Rifampin